2001
DOI: 10.1034/j.1399-5618.2001.030202.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent attentional dysfunction in remitted bipolar disorder

Abstract: The findings suggest that impairments in fine motor skills and reaction time may be present in clinically stable patients with BPD, even after accounting for psychiatric symptoms and medication effects. Performance decrements on attentional tasks may be in part reflective of motor impairments in patients with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 22 publications
8
69
1
5
Order By: Relevance
“…Findings in this research area indicate that euthymic patients commonly exhibit deficits on various measures derived from a range of sustained attention tasks (13,20,21,(23)(24)(25)(26); however, these impairments are not universal (11,27). As with the examination of executive deficits, it is possible that discrepant findings are at least partly due to different tests or measures that are employed across studies.…”
Section: Considerationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Findings in this research area indicate that euthymic patients commonly exhibit deficits on various measures derived from a range of sustained attention tasks (13,20,21,(23)(24)(25)(26); however, these impairments are not universal (11,27). As with the examination of executive deficits, it is possible that discrepant findings are at least partly due to different tests or measures that are employed across studies.…”
Section: Considerationsmentioning
confidence: 98%
“…Additionally, although more studies are needed in bipolar patients, the favourable cognitive profile of atypical antipsychotic agents is recognized in psychotic disorders such as schizophrenia and implied in bipolar disorder (60). The absence of association between medication dose and cognitive impairment in most studies of euthymic bipolar patients suggests that if medication side effects are present, they are relatively minor in magnitude and do not probably account for the full extent of cognitive impairment in euthymic bipolar disorder (6,9,13,14,16,18,20,24,26,30). Another potential confound that has received some attention is the influence of residual or subclinical mood symptoms on neurocognitive functioning in euthymic patients.…”
Section: Potential Confounds or Moderatorsmentioning
confidence: 99%
“…However, the NCI, with medians of 72.0, 73.5 and 67.5 for each [25][26][27][28][29][30][31][32][33][34][35] different types. In unipolar depression, impairment when present affected attention and concentration, learning, and in some cases, executive function 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested the presence of persistent cognitive impairments in patients diagnosed with BD even after prolonged euthymic phases [16,26,[40][41][42][43][44][45][46][47][48]. Review by Torres et al [4] revealed widespread cognitive deficits in tests assessing attention, speed of information processing, memory and executive dysfunctions in remitted bipolars versus controls.…”
Section: Cognitive Functions In Bipolar Patientsmentioning
confidence: 99%
“…Burdick [64] has not detected a direct relationship between attention deficits and depressive symptoms. Sustained attention deficits apparent during the euthymic period of bipolar disorder cannot be explained in terms of working memory impairment and represent a reduced inherent capacity rather than a changed response bias [16,42,44,45,53,65,66]. Sustained attention deficits are claimed to be a core deficit for bipolar disorder, but those deficits are not dependent on executive dysfunctions, including working memory.…”
Section: Cognitive Functions In Bipolar Patientsmentioning
confidence: 99%